2008
DOI: 10.3324/haematol.12319
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cytogenetic and molecular prognostic markers on the clinical management of chronic lymphocytic leukemia

Abstract: © F e r r a t a S t o r t i F o u n d a t i o nsubgroups for further analysis in microarray studies. Gene expression profiling revealed the association of a number of genes previously thought to be unrelated to CLL. Depending on the use of CD19-selected/T-cell depleted or unpurified B-CLL samples, a variety of markers have been found since the initial experiments of Klein and Rosenwald in 2001. 19,52-54 A comprehensive analysis of more than 500 patients suggests a complex expression pattern with many CLL sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 83 publications
0
12
0
2
Order By: Relevance
“…In this disease, chromosomal structural alterations as 17p deletion and point mutation of p53 gene have been reported in 10-15% of cases (6). These genetic abnormalities have been associated with poor survival and failure to therapy and they were reported in patients with transformation to Richter's syndrome, suggesting that p53 alterations play a role in this clinical adverse outcome (7,38). In addition, these genetic alterations result in poor response to fludarabine, a drug frequently used in CLL treatment (38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this disease, chromosomal structural alterations as 17p deletion and point mutation of p53 gene have been reported in 10-15% of cases (6). These genetic abnormalities have been associated with poor survival and failure to therapy and they were reported in patients with transformation to Richter's syndrome, suggesting that p53 alterations play a role in this clinical adverse outcome (7,38). In addition, these genetic alterations result in poor response to fludarabine, a drug frequently used in CLL treatment (38).…”
Section: Discussionmentioning
confidence: 99%
“…These genetic abnormalities have been associated with poor survival and failure to therapy and they were reported in patients with transformation to Richter's syndrome, suggesting that p53 alterations play a role in this clinical adverse outcome (7,38). In addition, these genetic alterations result in poor response to fludarabine, a drug frequently used in CLL treatment (38). The analysis of patients with CLL revealed that 14 of 64 patients with CLL had increased levels of p53 protein expression including eight of nine that progressed to Richter's syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the aberrant COX-2 expression is associated with disease progression suggesting a role in the malignant transformation. 4 In normal cells, COX-2 is an inducible key factor in prostaglandin synthesis and mediates inflammation by increased levels of prostaglandin. Ectopic expression of COX-2 and its downstream partner microsomal prostaglandin E synthase-1 (mPGES1) has been implicated in the pathogenesis of several cancer types, and the resulting production of prostaglandin E 2 (PGE 2 ) is known to sustain cancer progression by promotion of angiogenesis, invasion and metastasis.…”
Section: Letters To the Editormentioning
confidence: 99%
“…So far, gene expression profiling (GEP) in vivo in CLL was mainly used in a cross-sectional approach by studying patient samples before treatment. 4 We applied a sequential GEP (sGEP) approach to investigate the gene expression signature of CD19 þ selected CLL cells before and after treatment in vivo. This was complemented by protein analysis as well as by functional in vitro analysis of selected targets.…”
mentioning
confidence: 99%